The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/antiox10040572
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-CoA Metabolism and Histone Acetylation in the Regulation of Aging and Lifespan

Abstract: Acetyl-CoA is a metabolite at the crossroads of central metabolism and the substrate of histone acetyltransferases regulating gene expression. In many tissues fasting or lifespan extending calorie restriction (CR) decreases glucose-derived metabolic flux through ATP-citrate lyase (ACLY) to reduce cytoplasmic acetyl-CoA levels to decrease activity of the p300 histone acetyltransferase (HAT) stimulating pro-longevity autophagy. Because of this, compounds that decrease cytoplasmic acetyl-CoA have been described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 446 publications
(361 reference statements)
1
71
0
Order By: Relevance
“…Hypermethylation at the CpG island of the promoter region in ECM-related genes was induced by the long-term stimulation of PDLF with LPS [50]. Sodium acetate is immediately converted to acetyl-CoA by ACSS2 and used as an acetyl group for histone acetylation by HATs [51][52][53]. In the present study, the supplementation of acetyl-CoA, but not intermediate products, restored the si-PPARγ-dependent inhibition of osteo/cementogenesis (Figure 7).…”
Section: Discussionsupporting
confidence: 52%
“…Hypermethylation at the CpG island of the promoter region in ECM-related genes was induced by the long-term stimulation of PDLF with LPS [50]. Sodium acetate is immediately converted to acetyl-CoA by ACSS2 and used as an acetyl group for histone acetylation by HATs [51][52][53]. In the present study, the supplementation of acetyl-CoA, but not intermediate products, restored the si-PPARγ-dependent inhibition of osteo/cementogenesis (Figure 7).…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, the liver of Titan mice showed overall decreased H4 acetylation at the 4-17 motif, specifically histone acetylation motifs such as H4K16 and H4K12K16 acetylation, which is in correlation with a reduction in the expression of acetyl-CoA synthases (Accs2 and pdhx) which may imply reduced acetyl-CoA availability. This may underlie the general alteration in histone acetylation levels 39,66 and might also link this epigenetics phenotype to lifespan regulation 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is that SIRT-1, SIRT-2, SIRT-3, SIRT-6 and SIRT-7 are involved in recombinational and base excision DNA repair and maintenance of genomic stability, all important functions related to longevity [110] (Figure 2). It is well known that the inhibitions of other classes of histone deacetylases (HDAC) (i.e., class I, II, and IV) may delay ageing and promote longevity in experimental systems by, i.a., contributing to the maintenance of histone acetylation and genome stability [111]. As some natural organic selenium compounds can be biotransformed to keto acid HDAC inhibitors [112,113], this might also be a mechanism by which selenium could promote longevity.…”
Section: Selenium Genomic Stability and Telomere Lengthmentioning
confidence: 99%
“…A recent observational study indicated that dietary Se intake was related to longer telomeres in middle-aged and older adults in America [118]. These results were in accordance with observations by Wu et al, who showed that dietary Se deprivation induced telomere shortening in colonocytes of mice carrying humanized telomeres (G3 It is well known that the inhibitions of other classes of histone deacetylases (HDAC) (i.e., class I, II, and IV) may delay ageing and promote longevity in experimental systems by, i.a., contributing to the maintenance of histone acetylation and genome stability [111]. As some natural organic selenium compounds can be biotransformed to keto acid HDAC inhibitors [112,113], this might also be a mechanism by which selenium could promote longevity.…”
Section: Selenium Genomic Stability and Telomere Lengthmentioning
confidence: 99%